2013
DOI: 10.1186/1471-2458-13-632
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in reported psychosocial assessment across public and private maternity settings: a national survey of women in Australia

Nicole Reilly,
Sheree Harris,
Deborah Loxton
et al.

Abstract: BackgroundPsychosocial assessment and depression screening is now recommended for all women who are pregnant or have recently given birth in Australia. Existing studies which have examined the extent of participation by women in such population-based programs have been primarily concerned with depression screening rather than a more comprehensive examination of psychosocial assessment, and have not been sufficiently inclusive of the 30% of women whose maternity care is provided in the private sector. Whether t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 32 publications
2
42
0
Order By: Relevance
“…The actual assessment rate of 75% of all women who consented to participate was considered very good given the limitations of having a single part‐time (0.4FTE) research midwife to undertake all required assessments. For some domains of psychosocial health (including enquiry into mental health history and experience of abuse), the actual assessment rate was indeed higher than has been previously reported among national or Western Australian‐based respondents …”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The actual assessment rate of 75% of all women who consented to participate was considered very good given the limitations of having a single part‐time (0.4FTE) research midwife to undertake all required assessments. For some domains of psychosocial health (including enquiry into mental health history and experience of abuse), the actual assessment rate was indeed higher than has been previously reported among national or Western Australian‐based respondents …”
Section: Discussionmentioning
confidence: 56%
“…The study's collaborating perinatal mental health team provided timely clinical supervision to the assessing midwife and access to mental health referral, as required. While this and similar projects in private maternity settings represent important first steps, ongoing and meaningful engagement with both clinicians and consumers in this important sector is required if the potential challenges of embracing a comprehensive and inclusive approach to the delivery of routine psychosocial assessment in this context are to be met.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most women under private obstetric care in Australia (one‐third of the population) remain less likely to be routinely screened for psychosocial issues when booking in for pregnancy care (Reilly et al . ). A recent study found that when screened, one‐in‐ten women required referral for further assessment and support (Kohloff et al .…”
Section: Discussionmentioning
confidence: 97%
“…An additional limitation is that only one study included the private sector, which may offer a higher degree of continuity of care than public antenatal services. This is an under‐researched group, despite approximately 30% of Australian women choosing to access private obstetric care . Nevertheless, systematic reviews of this nature are valuable because they guide both research and policy regarding improved antenatal care services in the local context.…”
Section: Discussionmentioning
confidence: 99%